ANALYSIS OF MENTAL DISORDER OF THE MAIN CHARACTER IN JOKER’S FILM - Darwis, Muhammad Fairuz; Affandi, Akhmad; Nur, Muh. Safar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research aims to find out the mental disorders experienced by Artuhur Fleck and the causes of mental disorders experienced by Arthur Fleck. The main source of data for this research is the movie Joker (2019). Joker (2019) directed by Todd Philips and produced by Todd Philips, Bradley Cooper, and Emma Tilinger Koskoff. In this study, researchers examined mental disorders in joker movies through the character of Arthur Fleck. In researching mental disorders, researchers use the theory of Sigmund Freud (1900). The research method used is qualitative descriptive. This means that the data used in this study is qualitative data (data that does not consist of numbers) in the form of words and images that can be the key to what is being researched. Then the existing data is described from a number of aspects and signs or semiotics in a number of scenes. For example, in terms of the emotions that appear in a scene, the facial expressions of the actors, the dialogues conveyed by the actors.